Ocular Findings among the Patients of Renal Transplantation - Thapa, Madhu; Shrestha, Gulshan Bahadur; Gautam, Pragati; Sigdel, Mahesh Raj (Nepalese Journal of Ophthalmology, 2023)
Introduction: Renal diseases are on rise globally due to increased incidence of non-communicable diseases as well as primary-kidney diseases and frequent use of nephrotoxic drugs. Only definite treatment of End-Stage-RenalDisease (ESRD) is renal transplantation. Immuno-suppressive-drugs are prescribed lifelong after renal transplantation especially steroids which can lead to various sight-threatening complications.Methods: This cross sectional, observational study included 62 eyes of 31 patients who had undergone renal transplantation, at least 3 months prior were referred from Nephrology Department. Comprehensive eye evaluation was done at B. P. Koirala Lions Centre for Ophthalmic Studies (BPKLCOS), Department of Ophthalmology, Institute of Medicine.Results: The average age of participants was 37 ±10.57 years with 77.4 % (n=24) male. Mean duration of renal transplant was 5.10 ± 3.61 years. Fifty-eight percent (n=18) had hypertensive kidney disease. Diabetes Kidney disease, recurrent UTI, CKD of unknown causes and combined case of diabetes plus hypertension were seen in 6.4% (n=2) each. Sixty percent of the patients had some kind of ocular involvement. Twenty-nine percent (n=18) had subnormal visual acuity of ≤ 6/9. Cataract was seen in 29% (n=18) of eyes followed by pinguecula (17.7%, n=11) and hypertensive-retinopathy (17.7%, n=11). Glaucoma and Diabetic-retinopathy were seen only in 6.4% (n= 4) of each eyes. There was no association seen between ocular findings with cause of renal transplant, duration of transplant and renal function status in bivariate analysis.Conclusions: Some form of ocular abnormality is commonly seen in patients of renal transplantation who are on immunosuppressive drugs. However, incidence of sight threatening complications are rare.